Environmental Relations with Behavior of Adolescents Regarding HIV / AIDS in SMA Kambera Subdistrict, East Sumba Regency - Nyoko, Yuneti Octavianus; Hara, Maria Kareri; Abselian, Umbu Putal (JURNAL KESEHATAN PRIMER, 2018)
Background: In 2016 at East Sumba, there were 111 HIV / AIDS patients and the majority of productive age was 25-35 years old (51.4%) and most from Kambera District (28.8%). This study were aim to know the relation of environment with with HIV / AIDS Behavior Adolescent in Senior High School Kambera District, East Nusa Tenggara Regency. Methods: The study was analytic with crosssectional design. The population are 471 students class XI of Public Senior High School 1 Kambera, Christian Senior High School Payeti and Public Senior High School Vocational 5 Waingapu. The sample are 132 students who was selection with simple random sampling technique. The study was conducted in August 2017. The independent variable are environment and the dependent variable are behavior. The instrument used questionnaire. Analised data using univarait to know frekuensi and persentase also analised bivariate using chi-square. Results: 132 students were interviewebd and showed the majority are male (55.3%), 17 years old (50.8%), majority perents of farmer's (75,0%) with income ≤ regional minimum salary of East Sumba Rp. 1.250.000 (79.5%) and majotiry students had plan to continue the study after high school (77.3%). The majority environment of students are less good (63%) and behavior related to HIV / AIDS are less good (62.1%). The bivariate analysis showed a good environment related 3 times to good behavior related to HIV / AIDS in Kambera District Senior High School of East Sumba Regency and this relationship was statistically significant (PR = 2,625; 95% CI = 1,680-4,079; p-value <0.001). Suggested: School, community and family environments must give special attention to students and friendship of students environment so that it does not lead to less behavior especially HIV / AIDS.